2004
DOI: 10.1007/s00493-005-0010-x
|View full text |Cite
|
Sign up to set email alerts
|

List Colouring When The Chromatic Number Is Close To the Order Of The Graph

Abstract: Ohba has conjectured [7] that if G has 2χ(G)+1 or fewer vertices then the list chromatic number and chromatic number of G are equal. In this short note we prove the weaker version of the conjecture obtained by replacing 2χ(G) + 1 by 5 3 χ(G) − 4 3 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…The following lemma was proved independently by Kierstead [7], and by Reed and Sudakov [11,12], and named by Rabern. Pot Lemma).…”
Section: Set-upmentioning
confidence: 86%
“…The following lemma was proved independently by Kierstead [7], and by Reed and Sudakov [11,12], and named by Rabern. Pot Lemma).…”
Section: Set-upmentioning
confidence: 86%
“…For one, we show that for any minimal counterexample G, if G is not L-colorable, then the total number of colors in the union of the lists of L is at most 2k. This upper bound on the number of colors, foreshadowed in earlier work of Kierstead [12] and Reed and Sudakov [24,25], is crucial in that it implies the existence of colors that appear in the lists of many vertices, which our approach requires.…”
Section: Introductionmentioning
confidence: 91%
“…If any of the following are true, then G is chromatic-choosable. [25]); (c) |V (G)| ≤ (2 − ε)k − n 0 (ε) for some function n 0 of ε ∈ (0, 1). (Reed and Sudakov [24] [16]; Shen et al [26] proved the result for α ≤ 3).…”
Section: Introductionmentioning
confidence: 99%
“…The coloring algorithm, which we call Painter, must choose an independent set of marked vertices to receive that color. Colored Ohba [11] conjectured that G is chromatic-choosable when |V (G)| ≤ 2χ(G) + 1; after partial results in [8,11,12,14], this was proved by Noel, Reed, and Wu [10]. Various researchers (see [7]) observed that the complete multipartite graph K 2,...,2,3 is chromatic-choosable but not chromatic-paintable, so the paintability analogue is slightly different: Conjecture 1.2.…”
Section: Introductionmentioning
confidence: 99%